Determinants of Sustainability Report Quality: The Impact of Financial Performance, Corporate Governance, Firm Size, and Age - Reza Widya Saputra; Luh Gede Krisna Dewi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study empirically examines the impact of financial performance, corporate governance, firm size, and firm age on the quality of sustainability reporting. Using binary logistic regression analysis, the study processes data with SPSS version 26. The sample consists of 50 non-financial firms listed on the Indonesia Stock Exchange from 2018 to 2022, selected through a purposive sampling method, resulting in 250 firm-year observations. The findings indicate that independent commissioners, audit committees, and firm age positively influence sustainability report quality. However, liquidity, profitability, leverage, operational activity, board of directors, and firm size do not exhibit a significant effect.